Analisis Yuridis Normatif Perbandingan Prosedur Pemberhentian Presiden dalam Masa Jabatannya Antara Indonesia dengan Amerika Serikat dan Korea Selatan - Lintje Anna Marpaung (Law Faculty of Universitas Bandar Lampung, 2015)
The state is a phenomenon that is a legal entity that is a corporation, as a legal entity state is the personification of the order of national law which form a community, Impeachment president in the State of Indonesia, the United States and South Korea have fundamental differences that need to know how it compares to the dismissal of the president of the country. The main problem in this study include: a. Is the reason the president can be dismissed in his tenure. b. What is the ratio mechanism dismissal of the president in his tenure country of Indonesia, the United States and South Korea.The conclusion of this study are: (1). Reasons for the president may be dismissed in his term the constitution and other legal reasons. (2). Mechanism stops in the State Indonesia through the Parliament, the Constitutional Court, the Assembly, while in the United States House of Representatives as the Assembly of the Judge of the Senate as prosecutor general and the Chief Justice as chairperson in the proceedings of the congress, the South Korean National Assembly as a prosecutor while MK position as a determinant of whether the demands of the National Assembly canceled or not canceled.